Development of a novel hepatitis B virus encapsidation detection assay by viral nucleocapsid-captured quantitative RT-PCR - Ryu, Dong-Kyun (BioTechniques, 2015)
After encapsidation, where pregenomic RNA (pgRNA) is packaged into viral nucleocapsids, hepatitis B virus (HBV) uses the pgRNA as a template to replicate its DNA genome by reverse transcription. To date, there are only two encapsidation detection methods for evaluating the amount of pgRNA packaged into nucleocapsids: (i) the RNase protection assay and (ii) the native agarose gel electrophoresis assay. However, these methods are complex and laborious because they require multiple pgRNA purification steps followed by detection via an isotope-labeled probe. Moreover, both assays are unsuitable for evaluating a large number of antiviral agents in a dose-dependent manner. To overcome these limitations, we devised a novel HBV encapsidation assay in a 96-well plate format using nucleocapsid capture plates coated with an anti-HBV core (HBc) antibody, usually employed in enzyme-linked immunosorbent assays, to immobilize viral nucleocapsids. Viral pgRNA is then detected by quantitative RT-PCR (RT-qPCR). This strategy allows fast, convenient, and quantitative analysis of multiple viral RNA samples to evaluate encapsidation inhibitors. Furthermore, our protocol is potentially suitable for high-throughput screening (HTS) of compounds targeting HBV pgRNA encapsidation